Islamic Religious Education in Society 5.0: Developing Human-Centered Learning for Sustainable Future Competencies - Mahmoud Abdullah; Huzaiman Hushin; Salma Begum; Yousif Mahmadov; Abdallah El-Khatib (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
The Society 5.0 paradigm emphasizes the harmonious integration of advanced technologies with human-centered values to address increasingly complex societal challenges. Islamic Religious Education is expected to contribute not only to students’ religious understanding but also to the development of competencies required for sustainable human civilization. This study aims to formulate a human-centered Islamic learning model aligned with the principles of Society 5.0. A qualitative conceptual research design was adopted through literature synthesis, policy analysis, and expert consultation. The findings demonstrate that Islamic Religious Education can effectively promote creativity, critical thinking, collaboration, digital competence, ethical leadership, and social responsibility when integrated with contemporary pedagogical innovations. Furthermore, Islamic values provide a strong ethical foundation for balancing technological advancement with human dignity and environmental sustainability. The novelty of this study lies in developing the Society 5.0 Islamic Education Framework, integrating future competencies, technological literacy, sustainable development, and Islamic moral values into a comprehensive educational paradigm